Bacteriophages target membrane-anchored glycopolymers to promote host cell lysis and progeny release - Amelia C. McKitterick; Evan W. Lyerly; Thomas G. Bernhardt (Proceedings of the National Academy of Sciences, 2026)
Most bacteriophages lyse their host cell to release progeny virions. Double-stranded DNA phages typically promote host lysis using a holin-endolysin system. Holins form pores in the cytoplasmic membrane allowing endolysins access to the peptidoglycan (PG) cell wall, which they degrade to weaken the cell envelope and promote osmotic lysis. Phages that infect Proteobacteria also encode a spanin in their lysis cassette that functions to disrupt the host outer membrane (OM). The spanin-requirement for cell lysis provided the first clue that the proteobacterial OM confers mechanical rigidity to the cell envelope. Corynebacteria and mycobacteria also build an OM, but it is made of mycolic acids instead of lipopolysaccharides. Here, we investigated whether the mycomembrane presents a mechanical barrier to phage-induced lysis of corynebacteria. In addition to annotated holin and endolysin genes, mycobacteriophages and corynephages were found to encode a membrane protein we call LysZ in their lysis cassettes. Deletion of lysZ in the corynephage Cog blocked lysis of its host Corynebacterium glutamicum . Surprisingly, disruption of the host mycomembrane did not correct this phenotype. Instead, a genetic analysis revealed that blocking synthesis of membrane-anchored glycopolymers called lipomannans/lipoarabinomannans (LM/LAMs) can restore plaque formation when LysZ is inactivated. This genetic system also identified the likely flippase that transports decaprenyl-linked mannose units to the extracellular side of the membrane for polymerization into LM/LAM. Overall, our results indicate that lipoglycans like LM/LAMs play roles in mechanically stabilizing bacterial envelopes and that phages use LysZ-like factors to overcome this barrier to promote lysis.